The Corpo-Canovaccio: relationships between body and writing in contemporary Commedia Dell'Arte (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The concept of Corpo-canovaccio reflects how the actor's body transforms into a space layered with multiple cultural and narrative dimensions. From a contemporary perspective on Commedia Dell'Arte, the actor's body becomes a canvas that absorbs elements of improvisation, memory, and tradition. This article presents an autoethnographic study using the play O Soldado, a Tigresa e uma outra história, demonstrating how the Corpo-canovaccio facilitates the exploration of personal and cultural narratives while reinventing Commedia Dell'Arte. It also discusses Ma, a Japanese notion of suspended space-time, and the body in suspension, concepts that explain the constant transformation of the actor's body.
Keywords: Corpo-canovaccio; comédia dell'arte; autoethnography; dramaturgy; acting